The interpersonal benefits of goal adjustment capacities: the sample case of coping with poor sleep in couples - Barlow, Meaghan A.; Wrosch, Carsten; Hoppmann, Christiane A. (Frontiers in Psychology, 2024)
This study examined the role of goal adjustment capacities and coping in the association between spousal sleep efficiency and relationship satisfaction in romantic couples. A community lifespan sample of 113 heterosexual couples (age range = 21 to 82 years) was recruited using newspaper advertisements in the Greater Montreal Area from June 2011 to December 2012. Participants completed study measures (i.e., Goal Adjustment Scale [Wrosch et al., 2003], Brief Pittsburgh Sleep Quality Index [Buysse et al., 1989], Relationship Assessment Scale [RAS, Hendrick, 1988], and the Brief Cope [Carver, 1997]) at two time points, approximately one year apart. The results of actor-partner interdependence models with moderation (MIXED procedure in SPSS) reveal that goal disengagement buffered people from worsening relationship satisfaction associated with poor spousal sleep (95% CI B [-1.17, -0.12]), in part via increases in actor active coping (95% CI B [-0.32, -0.02]) and decreases in partner self-blame (95% CI B [-0.28, -0.01]). Goal reengagement was related to diminished relationship satisfaction in response to poor own sleep (95% CI B [0.59, 1.79]), in part through increases in actor behavioral disengagement (95% CI B [0.05, 0.41]). These findings point to a need for future studies to examine goal adjustment capacities and relationship-specific coping strategies as potential targets of intervention to maintain peoples’ relationship satisfaction in the face of sleep problems.